2023
DOI: 10.1039/d2sd00230b
|View full text |Cite
|
Sign up to set email alerts
|

Developing an electrochemical sensor for thein vivomeasurements of dopamine

Abstract: Measurements inside the human body are complicated. Here, we provide a short introduction of the main requirements for the successful in vivo determination of dopamine concentrations, together with a discussion...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 262 publications
0
1
0
Order By: Relevance
“…Although sensitive and selective detection of DA in the presence of the interfering species is possible using a screen-printed electrode (SPE) or glassy carbon (GC) electrode, detecting dopamine in attoliter droplets using an SPE or GC electrode is challenging due to the large capacitive current, which is proportional to the electrode area [48][49][50][51]. With UME having a micron-scale electroactive area, the dopamine in the attoliter vesicle can be detected.…”
Section: Resultsmentioning
confidence: 99%
“…Although sensitive and selective detection of DA in the presence of the interfering species is possible using a screen-printed electrode (SPE) or glassy carbon (GC) electrode, detecting dopamine in attoliter droplets using an SPE or GC electrode is challenging due to the large capacitive current, which is proportional to the electrode area [48][49][50][51]. With UME having a micron-scale electroactive area, the dopamine in the attoliter vesicle can be detected.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, studies have shown that more complex nanostructures are less susceptible to surface fouling [39,40]. However, with the rapid E2 signalling on neurons [41] like DA, the temporal and spatial resolution alongside biocompatibility must be considered for in vivo measurements in the brain [42]. Recently, E2 was characterized using fast-scan cyclic voltammetry (FSCV) [43] and co-detection with DA was achieved with a modi ed waveform [44] which satis ed the temporal and spatial requirements for both compounds.…”
Section: Introductionmentioning
confidence: 99%